Disfungsi Badan Usaha Milik Desa (BUMDes) dalam Pengembangan Otonomi di Wilayah Perbatasan - Sri Haryaningsih; Farah Devi Andriani; Ira Patriani (Jurnal Kawistara, 2022)
The stagnation experienced by BUMDes has not received serious attention from the government, even though BUMDes as a support for people's lives in rural areas need to be empowered to build village autonomy, especially in border areas. This paper aims to explain the complexity and dysfunction of BUMDes in achieving the goals of village autonomy. The data of this study were based on qualitative research collected through observation, interviews, and documentation studies. The results of the study showed that the limited space for community participation in planning and implementing policies is a factor that causes BUMDes to stagnate. In addition, the dysfunction of BUMDes occurs because the orientation of activities is more economic and political than community interests. Government policies that are not accommodating to the interests of villages in border areas further hamper the development of BUMDes. The solution that can be done is the cooperation of all parties in carrying out policies and a joint commitment to support village autonomy starting from the central, regional, and rural governments. Thus, the government's target to present a prosperous and empowered village face can be realized